PERAN DAERAH DALAM MENDUKUNG PASOKAN PANGAN NASIONAL - Suroso - Suroso (Jurnal Pangan dan Gizi, 2018)
Food supply is very important to ensure fullfilling the comsumption need of food for community. The objectives of the research are: (1) to analyze the food balance between the production and the consumption in the study area; and (2) to analyze the local government role in supporting national food supply. This research uses descriptive-quantitative approach. The research uses primary and secondary data. Data collecting is conducted by interview and survey. The analysis uses descriptive one.The research has 3 findings. Firstly, the local government of Pati Regency has a surplus balance for rice in average 237.030.630 kilograms annually.  Secondly, the local government through businessmen has roles for food supply (rice) to 5 provinces including: a) Bali; (b) Bogor, West Java; (c) Riau; (d) Lampung; and (e) Surabaya, East Java.  Thirdly, the local government through Bulog has a role for food supply (rice) to 7 provinces including: (a) Central Kalimantan; (b) East Kalimantan; (c) Kaltara; (d) West Sumatera Barat; (e) North Sumatera; (f) DKI Jakarta; dan (e) Banten.